GP61 Swollen eyes with an unpleasant surprise – a case report of a steroid resistant nephrotic syndrome. (June 2019) - Stanzelova, Anna; Krepelova, Anna; Nemcikova, Michaela; Zieg, Jakub
Abstract : With a reported incidence of 7:100 000, nephrotic syndrome (NS) is one of the more common nephrology disorders that can present to and is often treated by the general paediatrician in a primary and secondary level hospital. Standard treatment consists of steroids. Steroid resistant NS (SRNS) is an indication for renal biopsy. We present a case of a 5-year-old girl, who presented to a regional hospital at the age of 2.5 years, with periorbital oedema and abdominal swelling. Her medical history was significant for premature delivery, history of Intrauterine Growth Restriction (IUGR) and postnatal failure to thrive, persistent leucopoenia and mild developmental delay. Upon presentation she had marked proteinuria, serum hypoalbuminemia and hyperlipidaemia. A diagnosis of NS was made but she failed to respond to standard steroid treatment. She was transferred to a tertiary hospital on day 26 of admission with a suspicion of thrombophlebitis of her left lower limb. There, she was noted to have low set ears, areas of hyperpigmentation on her trunk, periorbital and limb oedema, ascites and abnormal posture. Pelvic X-ray showed bilateral hip dysplasia. Eye exam revealed retinal degeneration and blood investigations noted hypogammaglubulinemia, low CD4 and CD8 lymphocytes and high TSH. In view of her clinical picture, steroid resistant NS and leucopoenia, Shimke Immuno-Osseous dysplasia (SIOD) was suspected. SIOD is a rare autosomal recessive disease consisting of renal failure, skeletal dysplasia and T-cell deficiency. This was subsequently confirmed by genetic testing which showed 2 pathogenic mutations within the SMARCAL 1 gene. Overtime she progressed to end stage renal disease, and initiated peritoneal dialysis within a year of diagnosis. She remains to date without any major infectious, central nervous system (CNS) or autoimmune complications commonly seen in SIOD. The majority of paediatric patients with NS respond to steroid treatment. A subset of children might however have clinical and biochemical features or a family history predictive of a steroid resistant NS. Recent advances in molecular genetics identified underlying genetic cause in a large proportion of patients with SRNS. These children might benefit from an early referral to a tertiary centre in order to accelerate the diagnosis, potentially avoid renal biopsy and limit the exposure to steroids, which won't improve their condition. Rather they might increase their already elevated risk of infection and other complications.